TANGGUNG JAWAB PPAT DALAM HAL PEMBUATAN AKTA JUAL-BELI TANPA SEPENGETAHUAN AHLI WARIS - Jodhantara Aulliandika; Gunawan Djajaputra (Jurnal Hukum Adigama, 2019)
Land Deed Makers / PPAT Officers are officials who have the authority to make authentic deeds related to legal actions such as making land sale and purchase deeds. However, in practice, PPAT is often used as a part of the Defendant because of inaccuracy or inadvertence in making the sale and purchase deeds to the detriment of the heirs of the landowner. So the problem arises how the accountability of PPAT in terms of making Deed of Sale and Purchase without the knowledge of the Heirs of the Land? The method used is a normative legal research method. Based on PPAT Cikampek analysis results in decision number 12 / PDT.G / 2017 / PN.KWG declared to have committed acts against the law in carrying out their duties violating the precautionary principle of making Deed of Sale without the presence of Seller / heir so that, PPAT is dropped Article Acts against the law but without being held accountable, it should be in accordance with the provisions of Article 1365 of the Indonesian Criminal Code, a person who commits an act against the law is obliged to provide compensation, but in this decision the judge does not decide on the PPAT to be responsible but impose the article on illegal acts against PPAT with the regions Cikampek sub-district, Karawang Regency.